Behavior and personality psychological behaviorism - Staats, Arthur W. 1924- (Springer series on behavior therapy and behavioral medicine, 1996)
In this capstone work, Arthur Staats synthesizes more than four decades of research, theory, and study into a new generation of behaviorism that offers insights and future directions for researchers, professionals, and students. Staats's unified theory of psychological behaviorism builds on current theories in child development, personality, psychological measurement, and abnormal behavior. His theoretical model provides new ways to consider human behavior as a whole that will have implications for research, theory, and practice.